The effectiveness of physical activity interventions in improving well-being across office-based workplace settings: a systematic review - Abdin, S.; Welch, R.K.; Byron-Daniel, J.; Meyrick, J. (Public health (London), 2018)
Although the benefits of regular physical activity (PA) are widely accepted, most of the population fails to meet the recommended levels of activity. Public health bodies such as the World Health Organisation emphasise promoting PA within workplaces as a key intervention setting to reach the health and well-being of the working population. Given the importance of well-being in workplace settings, it seems worthwhile to explore the evidence of effectiveness in the literature. This systematic review aims to assess the effectiveness of PA interventions for improving psychological well-being in working adults. It provides a review of current evidence, assesses the quality of the research into this topic area and identifies issues and recommendations for future research. A systematic review guided by the Cochrane Handbook was conducted. PsycINFO, PubMed, ScienceDirect, Web of Science, Embase, MEDLINE and Cochrane Library literature searches were conducted from 2007 to April 2017. Using the keywords ‘Physical Activity’; ‘Exercise’; ‘Wellbeing’; ‘Employee’ and ‘Workplace’, five articles were obtained that fit the inclusion criteria. Inclusion criteria were a workplace setting, an intervention including a PA intervention and an outcome measure including well-being. Extraction of articles and quality assessment of the articles were performed independently by two authors using the Cochrane's data extraction form and the Cochrane's risk of bias. Owing to heterogeneity in population characteristics, intervention components, outcome measures and the durations of interventions, a narrative synthesis was conducted. The review identified five office-based workplace PA interventions in promoting psychological well-being in 1326 participants. The included studies varied substantially in sample size characteristics, methodological quality, duration of follow-up, types of interventions and assessed outcomes. Three of the five included studies were of high quality. The types of PA intervention included yoga, exercise and three studies focussing on walking interventions. The findings evidenced that exercise, yoga and walking interventions improve well-being as measured across workplace settings compared with no intervention. Some studies did not include a placebo control group and therefore, a form of PA intervention regardless of the type may be better than no intervention at all. This review found mixed evidence that PA interventions can be effective in improving well-being across office settings. Although, the findings are promising, because of methodological failings, there is no conclusive evidence. Current evidence indicates that employees can improve their psychological well-being by participating in any form of PA interventions in an office setting. •Physical activity interventions can be effective in improving well-being across office-based workplace settings.•All intervention types were able to elicit some improvement in psychological well-being vs control group.•Employees can improve their psychological well-being by participating in any form of physical activity interventions in an office setting.•The findings are promising; however, due to methodological failings, there is no conclusive evidence.•A need for better future research has been identifed.